The Effectiveness of the Let’s Teach for Hungary Mentoring Program - Kocsis, Nóra (Central European Journal of Educational Research, 2022)
The situation of disadvantaged students has been a problem in the field of education for decades, -so much so that several disadvantage-compensation programs have been set up in an effort to reduce its effect. This includes the mentoring process, the primary purpose of providing support and assistance to younger individuals. The subjects of the research are the 7th grade students participating in the Let’s teach for Hungary mentoring program. The questionnaire survey was conducted in the autumn of 2019 (n=585), during which I focused on the children’s expectations of the mentoring program, their learning difficulties, learning motivations, and their plans for further learning. Classifying students in clusters based on their motivations, highlights the fact that the range of participants is not homogeneous this aspect. The Coronavirus epidemic has posed a significant challenge to traditional education, and the opportunities offered by personal mentoring have been pushed into the background over the past year and a half. Educators and students alike have struggled through the transition to digital education (Kristóf, 2020). Attendance mentoring was forced to continue in the form of distance mentoring. In my current research, I examine the existence of distance mentoring, the exploration of experiences, and the preparedness of the participants in the Teach for Hungary program. Data collection began in December 2021, and the query process is still ongoing. I carry out the survey using a mixed-method. I collect quantitative data among students with the help of questionnaires, which focus on the experiences, opinions and readiness of the children. In addition, I use a qualitative, interview-based research method that provides an understanding of more comprehensive experiences. I conduct interviews with educators, mentors, and mentored students. The subjects of the research are primary school students (8th grade students), mentors and teachers of a small settlement in Hajdú-Bihar county and Szabolcs-Szatmár-Bereg county (n=60 people). The research results can serve as feedback to the participants on the success of work done during distance mentoring. The results obtained can also serve as feedback for the Let’s teach for Hungary program because the program can be developed in the future from interviews.